Depression Symptomatology and Anterior Cruciate Ligament Injury: Incidence and Effect on Functional Outcome—A Prospective Cohort Study. (March 2016) - Garcia, Grant H.; Wu, Hao-Hua; Park, Min Jung; Tjoumakaris, Fotios P.; Tucker, Bradford S.; Kelly, John D.; Sennett, Brian J.
Background: Recent literature has recognized a correlation with depression and poor self-reported functional outcome after orthopaedic procedures. However, the effect of depression on anterior cruciate ligament reconstruction (ACLR) outcome has never been studied. Purpose: To quantify the incidence of major depressive disorder (MDD) and correlate depression symptoms with patient-rated knee function in patients undergoing ACLR. Study Design: Cohort study; Level of evidence, 2. Methods: In this multicenter prospective cohort study, 64 consecutive adult patients undergoing primary ACLR were given the 16-item self-report Quick Inventory of Depressive Symptomatology (QIDS) to assess MDD symptoms preoperatively and at 6 weeks, 12 weeks, 24 weeks, and 1 year postoperatively. Lysholm and International Knee Documentation Committee (IKDC) subjective scores were obtained at the same time points to assess self-reported knee function. A QIDS score ≥6 served as a validated threshold for diagnosis of MDD. MDD and non-MDD group assignment was based on preoperative QIDS score. Student t test analysis was performed to compare ACLR outcomes between MDD and non-MDD patients. Correlation among QIDS, Lysholm, and IKDC scores was determined with Spearman r value. Results: A total of 27 patients (42%) were categorized in the MDD group. At baseline, the MDD group reported mean Lysholm (50.8) and IKDC (43.7) scores that were significantly lower than those (64.9 and 57.0, respectively) reported by the non-MDD group ( P < .05). Both cohorts showed similar and significant absolute improvement from baseline to 1 year postoperatively (MDD vs non-MDD, increase in mean Lysholm: +24.4 vs +23.5 [ P = .63]; MDD vs non-MDD, increase in mean IKDC: +28.1 vs +32.3 [ P = .21]). While Lysholm and IKDC scores improved in both groups, at 1-year follow-up, MDD patients reported significantly lower mean Lysholm (75.2 vs 88.4; P = .04) and mean IKDC (71.8 vs 89.3; P = .001) scores as compared with their non-MDD counterparts. In addition, a moderate inverse correlation was found between QIDS and Lysholm scores ( r = −0.50) and between QIDS and IKDC scores ( r = −0.54). Interestingly, 4 patients experienced complications in the MDD cohort (15%), while there were no complications in the non-MDD group. Conclusion: This study suggests that ACLR may be an equally effective intervention for MDD and non-MDD patients, given their similar significant absolute improvements in functional scores from baseline to 1 year after ACLR. However, MDD patients still reported significantly lower self-reported functional scores at baseline and 1 year postoperatively.